Flow behavior of Cu/CNTs feedstocks for powder injection molding - ., li Samer Muhsan, Faiz Ahmad, Norani Muti Mohamed, M Rafi Raza (2011)
In this study, the flow behavior of multi-walled carbon nanotubes (CNTs) reinforced copper matrix feedstocks is presented. The solid loadings in the copper feedstock were investigated in the ranges of 55-61 Vol. % using binder. Pure copper (Cu) and Cu/CNTs feedstocks were compounded using internal mixer machine for homoge nous dispersion of solids in the binder. The flow behavior was measured using a capillary rheometer in the shear rate range expected to occur during powder injection molding. An acceptable increasing trend in viscosity of the copper feedst ock with powder loading was recorded. Cu/CNTs composite feedstocks showed viscosity more than 1000 Pa.s which is most probably due to the addition of CNTs and increasing trend in viscosity of Cu/CNTs was noted as well. The results also identified that the feedstock containing 59 vol. % copper was most suitable for substitution of CNTs in Cu feedstock.